2015
DOI: 10.4172/2155-9821.1000203
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Lipase Production by Solid-State Fermentation

Abstract: Lipases are one of the most promising enzymes in the chemical and biopharmaceutical industries. Numerous applications have been reported including fine chemistry, detergents formulation and biodiesel synthesis. Lipases are commonly produced by a wide variety of yeasts and filamentous fungi in submerged fermentation or solid-state fermentation. Filamentous fungi and yeasts usually behave more efficiently in solid-state fermentation and show greater productivities when compared to submerged fermentation. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 86 publications
1
30
0
6
Order By: Relevance
“…Water activity is a fundamental parameter in the mass transfer of water and nutrients through the microbial cells (Pandey, 2003;Ramos-Sánchez et al, 2015). The values of a w and pH at the beginning and at the end of the fermentation are listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water activity is a fundamental parameter in the mass transfer of water and nutrients through the microbial cells (Pandey, 2003;Ramos-Sánchez et al, 2015). The values of a w and pH at the beginning and at the end of the fermentation are listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen sources (organic and inorganic) used to supplement the culture medium greatly influence lipase production (Ramos-Sánchez et al, 2015). Agro-industrial wastes, besides serving as a support for microbial growth, serve as a source of nitrogen.…”
Section: Lipase Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipases or triacylglycerol acyl ester hydrolases belong to the serine hydrolase family; they are called carboxylic acid esterases, numbered as EC 3.1.1.3, and are a group of enzymes that are abundantly present in nature . Most of the lipases are built on α/β hydrolase fold composed of a core of predominantly eight parallel β strands forming a super‐helically twisted central β sheet surrounded by varying number of α helices.…”
Section: Lipase Structure and Classificationmentioning
confidence: 99%
“…It is to be observed that these fungal lipases can catalyze a wide range of reactions including hydrolysis, esterification, transesterification, deacetylation, alcoholysis, acidolysis, saponification, ethanolysis, hydrolytic kinetic resolution, etc. Recent advances reported on fungal lipases highlight solid‐state fermentation as a promising technology for their production . The molecular and functional diversity of the fungal lipases are detailed in another review in which the multidisciplinary approaches for designing novel enzyme variants that resulted in improved thermo‐stability and substrate specificity are discussed in .…”
Section: Sources Of Lipasesmentioning
confidence: 99%